Timurnesia: Rekonstruksi Identitas Kolektif dan Kedaulatan Kreatif dalam Rimba Algoritmik Musik Indonesia Timur - Muhammad Ilham Mustain Murda; Zandry Aldrin (Grenek: Jurnal Seni Musik, 2026)
The increasing public attention to Eastern Indonesian music in the digital space has not been fully followed by equal recognition in national music policy, distribution, and industry. This study analyzes Timurnesia as a reconstruction of collective identity and an initial strategy for strengthening the creative richness of Eastern Indonesian music amidst industry centralization and the dominance of digital platforms. The study uses a qualitative approach with a reflective autoethnography method. The primary data comes from the author's field notes as a participant in the Focus Group Discussion "Roadmap for the Eastern Indonesian Music Ecosystem in National Cultural Policy" held by the Indonesian Ministry of Culture on January 27, 2026. Data are strengthened through forum documents, reflective memos, media, and digital traces. The results of the study indicate that Timurnesia is not simply a genre name, but a community forum and framework that consolidates Eastern Indonesian music practitioners. The study concludes that Timurnesia is still in the early stages of institutionalization, but has the potential to strengthen regional identity, digital resilience, and community-based cultural diplomacy